Ազգությանը և ազգայինին վերաբերող բառերը հայաստանյան մամուլի հրապարակախոսության լեզվում (1990-ական թվականների սկիզբ) - Բալոյան, Հրաչյա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В языке публицистики армянской прессы 1991–1993 гг. многочисленны новообразованные слова, относящиеся к национальности, национальному. Среди них доминируют слова, состоящие из компонента ազգ (нация). В числе последних есть прилагательные, образованные по шаблону ազգ (нация)+простое существительное, где субстантивные окончания выражают причастные значения. Некоторые слова образованы по шаблону нация+ отглагольное существительное (с суффиксом-ում) (-е՛ние, -а՛ние). Ряд слов составлены по шаблону ազգ (нация)+существительное (с суффиксом –ություն) (-ность). Имеем также слова, образованные по шаблону ազգ (нация)+прилагательное. С компонентом ազգ (нация) нам встретился только один глагол. Были образованы также слова другого рода с суффиксом – ություն (-ность). Есть три слова, образованные элементом էթն(ոս) (этн(ос)). Некоторые слова, относящиеся к армянам, образованы по шаблону հայ (армянин) + существительное (или отглагольное имя). В этой смысловой подгруппе имеем также слова по шаблону названия страны, населенного пункта, административной единицы + հայ (армянин, армянский). Некоторые из неологизмов, связанных с русской нацией, образованы по шаблону ռուս (русский) + существительное (со значением имеющй что-то). Шаблон некоторых – ռուս (русский) +глагольный корень, в смысле субъектного причастия. Есть также слова, образованные по шаблону ռուս (русский)+существительного (с суффиксом –ություն) (ность). Среди неологизмов, относящихся к русской нации, есть и инос- транные слова. Некоторые слова, относящиеся к другим нациям, составлены по шаблону название нации + ացնել (-изировать). Шаблоном некоторых слов является название народа (+ական (-ский))+ացում (-ация). В этот ряд также входят слова с окончанием -ազգի (-нация). Встречаются также слова с компонентом կիս(ա)- (полу-), а также новообразования с суффиксом -ուհի (-ка). There are numerous newly formed words related to nationality and national in the language of journalism of the Armenian press for the period from 1991 to 1993. Among the words related to nationality and national, the words consisting of the component ազգ (nation) dominate. Among the latter, there are adjectives that are composed of nation + simple noun pattern, where the noun endings express a participial meaning. Some words are formed in the pattern nation + verbal noun (with the suffix -ում (the same as -tion in English)). A number of words were formed in the pattern nation + noun (with the suffix –ություն (the same as -ity in English). We also have newly formed words composed of ազգ (nation) + adjective pattern. We have encountered only one verb with the component ազգ (nation). Some words of another kind were also composed with the suffix – ություն (the same as -ity in English). There are three words formed by the component էթն(ոս) (ethnos (ethnicity)). Some of the words referring to Armenians are composed according to the pattern հայ (Armenian) + noun (or verbal noun). In this semantic subgroup, we also have words in the pattern the name of the country, settlement, administrative unit+ հայ (Armenian). Some of the newly formed words related to the Russian nation are formed in the pattern ռուս (Russian) + noun (with the meaning ‘having something’). The pattern of some is ռուս (Russian) + verbal root in the meaning of subjective participle. There are also words composed of the pattern ռուս (Russian) + noun (with the suffix – ություն (the same as -ity in English)). There are also foreign words among the neologisms related to the Russian nation. Some of the words referring to other nations are formed according to the pattern nation name + ացնել (the same as -ize, -ify in English). The pattern of some words is the name of the nation (+ական)+ ացում (the same as (+ian) +tion in English). This line also includes words with the ending - ազգի (the same as -ian in English). There are also words with the component կիս(ա) (the same as -semi in English) and some neologisms with the suffix - ուհի (Armenian suffix for females).
Keywords: Լեզվաբանություն